EVALUATION AND COMPARISON EFFICIENCY OF THE TROCAR AND TROCAR FREE METHODOLOGY OF RECONSTRUCTION OF THE FRONT AND APICAL COMPARTMENTS OF THE PELVIC FLOOR USING SYNTHETIC MESH WITH PELVIC PROLAPSE - Pliss, Mikhail; Gorelov, A.; Peshkov, N.; Gorelova, A. (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2019)
Pelvic floor reconstruction with vaginal access using synthetic mesh is a common and effective approach to the treatment of pelvic prolapse positive forms. The current stage in the mesh pelvic surgery development is the best-practice implant placement technique emergence - SIMS (single-incision mesh system). SIMS fundamental differences: mesh system fixing with harpoon elements (anchor) to the most durable connective tissue structures of the pelvis (sacrospinal ligament, obturator membrane); less traumatization due to the absence need to carry out trocars through the pelvic surface tissues. According to the recent studies (Lukban JC et al., 2012; RD Moore et al., 2012; EJ Stanford et al., 2013), objective efficacy of the Elevate ™ system using during the year with anterior plastic is from 88% to 92%, the apical - from 89% to 96%, back to 93% [1,2,3]. Comparing SIMS with traditional mesh plastic (210 patients, the follow-up period is 1 year): the anatomical efficiency for the anterior part was 98% versus 87% (p = 0.006), for the apical 99% versus 96% (p = 0.317), and for the posterior 100% versus 97% (p = 0.367) [4]. Nevertheless, there are questions about the reliability of harpoon elements fixing and the new operational methodology safety remain.